Relationship between farmers’ knowledge and attitudes towards pesticide use and their sociodemographic characteristics: a cross-sectional study from north-western Turkey - Celalettin Cevik; Raziye Ozdemir; Sezgin Ari (Roczniki Panstwowego Zakladu Higieny, 2020)
Background. The determination of farmers' knowledge and attitudes towards pesticide use is very important in terms of preventing pesticide use-related short- and long-term damages. Objective. This study was aimed at investigating the relationship between the sociodemographic characteristics of farmers in Karacabey District of Bursa, a province in northwest Turkey, and their knowledge and attitudes towards pesticide use. Material and methods. This cross-sectional study was conducted in Karacabey district between December 2018 and April 2019. The sample size was calculated as 1924 using the Epi info program by assuming the prevalence as 50%, type I error as 5%, standard deviation as 3% and design effect as 2. The dependent variable of the study was the farmers' knowledge of and attitudes towards pesticide use whereas the independent variables were their sociodemographic characteristics. The relationship between the dependent and independent variables was analyzed using the chi-square test and binary logistic regression model. Results. The mean score the participants obtained from the Knowledge and Attitude Index was 12.8±2.8 and the median value was 13. While 49.5% of the participating farmers obtained a score lower than the median, 51.5% of them obtained a score equal to or above the median. While advanced age increased the possibility of getting a low score from the Knowledge and Attitude Index 2.7 times, not being married increased it 35.7 times, not getting formal education increased it 30.1 times, living in a non-crowded household increased it 2.1 times, and low income (2000 Turkish liras equal to ≤$310 according to April 2019 exchange rates) increased it 3.1 times. Conclusion. The study indicated that the participating farmers’ knowledge and attitudes towards the proper use of pesticides were inadequate, and that there was a strong relationship between their Knowledge and Attitude Index scores and their sociodemographic characteristics.